(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
This article studies the effects and consequences of marshallagiosis, nematodirosis, and habertiosis helminthiases on the dynamics of quantitative changes of some macroelements (K, Na, Ca) in the blood composition of Karakul lambs.